Virtual Screening and Molecular Modelling Anticancer Molecules Targeting Fibroblast Growth Factor Receptor 4 - Rosa, Feby Lilia; Fadilah, Fadilah; Erlina, Linda (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Cancer, characterized by uncontrolled cell proliferation, is a leading global cause of mortality. Targeting the fibroblast growth factor receptor (FGFR), a receptor tyrosine kinase (RTK), holds promise for anticancer drug development. FGFR4, a specific subtype, regulates various cellular processes, making it a valuable target. In-silico methods were employed to screen 20 compounds against FGFR4 (PDB ID 5JKG) using AutoDock Version 4.2.6. The top three potential inhibitors, based on Gibbs energy (Î”G) and inhibition constant (Ki), were identified: epigallocatechin3-O-pcoumarate (Î”G = -10.46 kcal/mol; Ki = 21.37 nM), 6_deoxoteasterone (Î”G = -10.22 kcal/mol; Ki = 32.35 nM), and epigallocatechin3-O-caffeate (Î”G = -9.78 kcal/mol; Ki = 68.16 nM). ADMETOX analysis confirmed compliance with Lipinski's rules, indicating their safety. These compounds show promise as FGFR4 inhibitors, potentially as standalone therapy or in combination with other anticancer drugs.